Divergent thinking in the grasslands: thinking about object function in the context of a grassland survival scenario elicits more alternate uses than control scenarios. Issue 5 (3rd July 2016) - Wilson, Stuart
ABSTRACT: The survival processing effect is a recall advantage for information processed in the context of a grassland survival scenario. The current studies build upon previous research suggesting the effect is due to elaborative encoding and functional thinking. In two experiments, participants completed the "alternate uses test" under five conditions: baseline, grassland survival, Ebola survival, moving to a new home and planning a bank heist. Experiment 1 stimuli were everyday objects. Experiment 2 stimuli were functionally ambiguous "mystery" objects. Number of generated uses was highest in the baseline, but the grassland scenario was consistently highest of the schematic conditions. Recall data lend support to the mnemonic superiority of the grassland condition. Results suggest that grassland scenarios place fewer attenuating constraints on divergent thinking. It is suggested that the survival processing effect might be usefully conceptualised as an effect of creatively thinking about object function in response to broadly defined problems.